ON SYNONYMICS OF COAL SEAMS AND LIMESTONES OF THE CARBONIFEROUS SYSTEM OF THE LVIV-VOLYN BASIN - Kostyk, I.O.; Buchynska, I.V.; Korol, M.D.; Poberezhsky, A.V. (Institute of Geological Sciences, NAS of Ukraine, 2020)
The results of regulation of synonymics of coal seams and limestones of the Carboniferous system of the Lviv-Volyn Basin taking into account ratified changes in its stratigraphic section are presented. It was noted that indices of coal seams appropriated by the previous investigators are out of accordance with the names of stages in the stratigraphic section of deposits of the Carboniferous system of the basin that were changed by the resolution of the Interdepartmental Stratigraphic Committee (ISC) of the USSR in 1974 and ISC of Ukraine in 2013.On the basis of detailed analysis and systematization of factual material and interpretation of logging data from prospecting holes of the coal fields of the basin the regulation of synonymics of coal seams and limestones was carried out in conformity with changes in the names of the stages in the stratigraphic section of the Carboniferous system or their age succession. The classification of the synonymics of Lviv-Volyn Basin is based on the notation corresponding to the names of the selected stages (their initial letters). In accordance with such a concept, the indexation of coal seams of the Visean stage begins with the lower layer of coal in the sediments of the Kulychkivska suite of the early Visean. The synonymics of coal seams and limestones of the Serpukhovian stage is replaced by the letters s and S, respectively. The synonymics of coal seams and limestones in the deposits of the Buzhanska suite, which refers to the Bashkirian stage of the Middle Carboniferous, is also replaced by the letters b and B. The system indexation we have conducted will allow us to develop a substantially updated indexing scheme for coal seams and limestones of Lviv-Volyn Basin coal deposits, which fully complies with the stratigraphic classification standards, has both scientific and applied value and is recommended for consideration and approval by ISC of Ukraine.